Application of Nanomaterials Targeting Immune Cells in the Treatment of Chronic Inflammation - Ci Z; Wang H; Luo J; Wei C; Chen J; Wang D; Zhou Y (International Journal of Nanomedicine)
Zhen Ci,1,2,* Hanchi Wang,1,2,* Jiaxin Luo,1,2 Chuqiao Wei,1,2 Jingxia Chen,1,2 Dongyang Wang,2,3 Yanmin Zhou1,2 1Department of Oral Implantology, Hospital of Stomatology, Jilin University, Changchun, 130021, People’s Republic of China; 2Jilin Provincial Key Laboratory of Tooth Development and Bone Remodeling, Hospital of Stomatology, Jilin University, Changchun, 130021, People’s Republic of China; 3Department of Oral Biology, Hospital of Stomatology, Jilin University, Changchun, 130021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanmin Zhou, Department of Oral Implantology, Hospital of Stomatology, Jilin University, Changchun, 130021, People’s Republic of China, Email zhouym@jlu.edu.cn Dongyang Wang, Department of Oral Biology, Hospital of Stomatology, Jilin University, Changchun, 130021, People’s Republic of China, Email dyang314@jlu.edu.cnAbstract: Chronic inflammation is a common characteristic of all kinds of diseases, including autoimmune diseases, metabolic diseases, and tumors. It is distinguished by the presence of low concentrations of inflammatory factors stimulating the body for an extended period, resulting in a persistent state of infection. This condition is manifested by the aggregation and infiltration of mononuclear cells, lymphocytes, and other immune cells, leading to tissue hyperplasia and lesions. Although various anti-inflammatory medications, including glucocorticoids and non-steroidal anti-inflammatory drugs (NSAIDs), have shown strong therapeutic effects, they lack specificity and targeting ability, and require high dosages, which can lead to severe adverse reactions. Nanoparticle drug delivery mechanisms possess the capacity to minimize the effect on healthy cells or tissues due to their targeting capabilities and sustained drug release properties. However, most nanosystems can only target the inflammatory sites rather than specific types of immune cells, leaving room for further improvement in the therapeutic effects of nanomaterials. This article reviews the current research progress on the role of diverse immune cells in inflammation, focusing on the functions of neutrophils and macrophages during inflammation. It provides an overview of the domestic and international applications of nanomaterials in targeted therapy for inflammation, aiming to establish a conceptual foundation for the utilization of nanomaterials targeting immune cells in the treatment of chronic inflammation and offer new perspectives for the avoidance and management of inflammation. Keywords: nanomaterials, periodontitis, chronic inflammation, target therapy, neutrophil, macrophage